Concise Review: Deconstructing the Lung to Reveal Its Regenerative Potential123. (9th April 2012) - McQualter, Jonathan L.; Bertoncello, Ivan
Abstract: Despite burgeoning interest in the potential of cellular therapies in lung regenerative medicine, progress in delivering these therapies has been confounded by a lack of knowledge about the identity of appropriate targets which can be harnessed to repair the lung, and the cellular and molecular factors which regulate their regenerative potential. While systematic analysis of lung development and cell lineage tracing studies in normal and perturbed animal models provides a framework for understanding the complex interplay of the multiple cell types, biomatrix elements and soluble and insoluble cytokines and factors that regulate lung structure and function, a reductionist approach is also required to analyze the organization of regenerative cells in the adult lung and identify the factors and molecular pathways which regulate their capacity to generate descendent lineages. In this review we describe recent progress in identifying and characterizing endogenous epithelial, mesenchymal and endothelial stem/progenitor cells in the adult lung using multiparameter cell separative strategies and functional in vitro clonogenic assays. STEM CELLS 2012;30:811–816